Breast adenomyoepithelioma with ductal carcinoma in situ: An unusual entity (Indian Journal of Case Reports, 2021)
Adenomyoepithelioma is a rare biphasic tumor characterized by the proliferation of inner glandular epithelial cells and outer myoepithelial cells. These tumors have a low-grade potential for local recurrence and malignant transformation. Here, we present the case of a 51-year-old female who presented with a right breast lump for 1 month. Mammography was suggestive of BIRADS 4/5 for the right breast while BIRADS 1 for the left breast. FNAC was reported as benign breast disease, whereas, trucut biopsy of the same lesion was suggestive of invasive ductal carcinoma with ductal carcinoma in situ (DCIS). A final diagnosis of adenomyoepithelioma with DCIS component was confirmed on the right modified radical mastectomy. We, hereby, describe an extremely unusual case of biphasic breast adenomyoepithelioma that depicted benign features on FNAC and features of an invasive ductal carcinoma on trucut biopsy. Its distinct histomorphology with a characteristic epithelial-myoepithelial immunohistochemical profile on modified radical mastectomy specimen led to a definitive diagnosis of adenomyoepithelioma with DCIS.